Key Milestones in Urban Operations - Claudiu Valer NISTORESCU (Bulletin of "Carol I" National Defense University)
Both the Russian-Ukrainian war and the conflict in the Gaza Strip underline the importance of the cities and urban terrain in combat operations. The battles for Kiev, Mariupol, Bakhmut, Gaza, and Rafah demonstrate the scale, intensity, and ferocity of the combatants’ actions, as well as the sensitivity of the operational process in the context of a transparent and highly contested operational environment. The new demands of today’s operational environment require adjustments to the planning process preparing and execution of the military operations. The urban environment, by its specificity, generates a series of implications for combat operations, which become essential benchmarks of the operational process. In this context, the objective of this paper is to identify and describe the milestones of the operational process related to urban operations. While the results of the research offer empirical solutions, their value is enhanced by the theoretical contribution they make to tactical-level commanders in terms of the approach to this type of operation.